Creating a Benevolent World: Exploration of a Music-Based Rehabilitation Program for Formerly Incarcerated Individuals - Bensimon, Moshe (International journal of offender therapy and comparative criminology, 2024)
Many studies discuss the impact of music programs on prison inmates. However, few studies have investigated the impact of music programs on formerly incarcerated individuals (FIIs), and none of them have focused on the programs’ characteristics. This phenomenological study explores the characteristics of a music-based rehabilitation program for FIIs. Five FIIs and three staff members who participated in a group music program were interviewed. The following four themes emerged: Continuity—the importance of the FIIs’ previous positive acquaintance with the program while still being in prison. Egalitarian approach—the importance of the staff treating the FIIs with understanding, tolerance, non-judgmentalism, and the use of an eye-level approach. Cultural sensitivity—the staff members’ sensitivity to the FIIs’ different backgrounds to form a connection. Playfulness—the program’s ability to break free from a “fight-or-flight” mode and experience a counter mode of playfulness. The findings are discussed through the perspective of positive criminology.